EFFECTS OF AUSTENITIZATION ON STRUCTURE FORMATION СHROMO-MOLYBDENUM-VANADIUM STEEL AFTER HIGH TEMPERING - V. A. Lutsenko; T. N. Golubenko; O. V. Lutsenko; N. A. Glazunova (Литьë и металлургия)
Influence of austenitization temperature of chrome-molybdenum-vanadium steel on structure formation at the softening heat treatment is studied. It is shown that the decline of the austenitization temperature promotes to reduce the micro-hardness values due to the intensification of spheroidizing of pearlite after the overcooling and high tempering. Increasing the austenitization temperature leads to formation of an uneven structure after tempering.